A brief overview on the application and sources of α‐amylase and expression hosts properties in order to production of recombinant α‐amylase. (19th March 2021) - Movahedpour, Ahmad; Asadi, Marzieh; Khatami, Seyyed Hossein; Taheri‐Anganeh, Mortaza; Adelipour, Maryam; Shabaninejad, Zahra; Ahmadi, Nahid; Irajie, Cambyz; Mousavi, Pegah
Abstract: By reducing the activation energy, enzymes accelerate the chemical reaction; therefore, they are good alternative for industrial catalysts. Amylase is a suitable enzyme as a catalyst for the chemical decomposition of starch. This enzyme is of great importance, and its production is highly profitable. α‐Amylase is among the most important amylases produced naturally by animals, plants, and microorganisms. Still, the α‐amylases produced by bacteria have a special place in industry and commerce. Moreover, a large volume of this enzyme can be produced by selecting an appropriate and optimized host to clone and express the α‐amylase gene. The present study briefly reviews the structure, application, sources, and hosts used to produce recombinant α‐amylase.